Patients’ Needs on Nutritional Counseling and Risk Factor Management Among Myocardial Infarction Patients in Cardiac Rehabilitation - Yusshy Kurnia Herliani; Urip Rahayu; Chandra Isabella Hostanida Purba; Hasniatisari Harun (Journal of Nursing Care, 2019)
The needs of nursing care for Myocardial Infarction (MI) patients who performing Cardiac Rehabilitation (CR) Program have been investigated previously. Despite, nutritional counseling and risk factors management were reported as the most needs of MI patients who performed CR Program, information related to the MI patients’ needs on nutritional counseling and risk factor management are very limited. Moreover, the relationship between patients’ needs on nutritional counseling and risk factor management are not clear yet. To investigate patients’ needs on nutritional counseling and risk factor management among MI patients and its relationships those factors. This was quantitative approach with descriptive correlational and convenience sampling was used for this study. The participants included 38 MI patients admitted to the Cardiac Rehabilitation Unit. Data collection employed from questionnaires that were filled in by the respondents using a retrospective technique at the end of cardiac rehabilitation program.  Data were analyzed using descriptive and correlational statistics. The study signified that MI patients required cardiac rehabilitation towards risk factors management and nutritional counseling from nurses (92.1%).The finding also indicated that there is a statistically positive relationship between nutritional counseling needs and risk factor management (r = 0.503, p <0.01). Patients’ needs on nutritional counseling and risk factor management among MI patients are correlated positively. Therefore, the information regarding nutrition and risk factor management for MI patients should be provided simultaneously to complement each other.